Examination of personality correlates, exercise preferences, and exercise behavior / Amy L. Hagan and Heather A. Hausenblas - Hagan, Amy L.; Hausenblas, Heather A. (Faculty of Sports Science and Recreation, 2005)
Researchers have found that personality is a determinant of exercise behavior. Limited exercise studies however, have used the dominant personality framework of the Five Factor Model (FFM) which asserts that personality consists of the following 5 domains: neuroticism, extraversion, openness, agreeableness, and conscientiousness. The purposes of this study were to examine: (a) if the personality domains of the FFM are related to and predict exercise behavior, (b) if the personality domains are related to exercise preferences and barriers-efficacy, and (c) if gender moderates the relationship between personality and exercise. Participants were 507 male and female undergraduates who voluntarily completed the NEO PI-R (Costa & McCrae, 1992), the Leisure Time Exercise Questionnaire (Godin, Jobin, & Bouillon, 1986), Barriers-efficacy Scale (McAuley & Mihalko, 1998), and preferences to exercise. Results revealed that: (a) extraversion, conscientiousness, and agreeableness were positively related to exercise behavior; (b) significant differences for personality domains and preferences appeared for exercise intensity, exercise company, and gym preference; (c) barriers-efficacy was positively related to openness and conscientiousness and negatively related to neuroticism; and (d) the relationships between personality and exercise were moderated by gender. Applying the FFM to explain exercise preferences and behavior and future research directions were discussed.